Free‐breathing diffusion tensor MRI of the whole left ventricle using second‐order motion compensation and multitasking respiratory motion correction. Issue 5 (30th November 2020) - Nguyen, Christopher T.; Christodoulou, Anthony G.; Coll‐Font, Jaume; Ma, Sen; Xie, Yibin; Reese, Timothy G.; Mekkaoui, Choukri; Lewis, Gregory D.; Bi, Xiaoming; Sosnovik, David E.; Li, Debiao
Abstract : Purpose: We aimed to develop a novel free‐breathing cardiac diffusion tensor MRI (DT‐MRI) approach, M2‐MT‐MOCO, capable of whole left ventricular coverage that leverages second‐order motion compensation (M2) diffusion encoding and multitasking (MT) framework to efficiently correct for respiratory motion (MOCO). Methods: Imaging was performed in 16 healthy volunteers and 3 heart failure patients with symptomatic dyspnea. The healthy volunteers were scanned to compare the accuracy of interleaved multislice coverage of the entire left ventricle with a single‐slice acquisition and the accuracy of the free‐breathing conventional MOCO and MT‐MOCO approaches with reference breath‐hold DT‐MRI. Mean diffusivity (MD), fractional anisotropy (FA), helix angle transmurality (HAT), and intrascan repeatability were quantified and compared. Results: In all subjects, free‐breathing M2‐MT‐MOCO DT‐MRI yielded DWI of the entire left ventricle without bulk motion‐induced signal loss. No significant differences were seen in the global values of MD, FA, and HAT in the multislice and single‐slice acquisitions. Furthermore, global quantification of MD, FA, and HAT were also not significantly different between the MT‐MOCO and breath‐hold, whereas conventional MOCO yielded significant differences in MD, FA, and HAT with MT‐MOCO and FA with breath‐hold. In heart failure patients, M2‐MT‐MOCO DT‐MRI was feasible yielding higher MD, lower FA, and lower HAT compared with healthy volunteers. Substantial agreement was found between repeated scans across all subjects for MT‐MOCO. Conclusion: M2‐MT‐MOCO enables free‐breathing DT‐MRI of the entire left ventricle in 10 min, while preserving quantification of myocardial microstructure compared to breath‐held and single‐slice acquisitions and is feasible in heart failure patients.